Enhanced Hydrogen Production during Electro‐Oxidation of Ethanol using Plasmonic Gold Nanoparticles. Issue 10 (12th August 2022) - Mahanta, Jiwajyoti; Basak, Mitali; Parmar, Prathu Raja; Saha, Devi Rupa; Mandal, Tapas Kumar; Bandyopadhyay, Dipankar
Abstract : Electrochemical reforming of alkaline ethanol through nonfossil fuel resources is an attractive single‐step method at room temperature and pressure for hydrogen production. Herein, solar panels are used to generate and allow low‐voltage current to flow into screen‐printed electrodes with milliscale spacing to produce a high‐intensity electric field, engendering electrolysis of alkaline ethanol into H2 . The introduction of gold nanoparticles (Au NPs) with diameters between 20 and 100 nm into the electrolyte results in an enhanced capacity of the electrolyzer to produce H2 under an illumination equivalent to solar irradiance. The plasmonic Au NPs facilitate faster electro‐oxidation of the alkaline ethanol. The solar irradiance serves dual purposes—generation of a high‐intensity electric field in the electrolyte and plasmonic effects for a faster rate of H2 production. The results show current densities as high as 135, 240, and 118 A m −2 with independent variations in sizes of Au NPs, wavelength of solar radiation, and irradiance of light, respectively. Furthermore, a high Faradaic efficiency of 82% is obtained for the electrolyte solution containing Au NPs of size 50 nm. Integration of multiple screen‐printed electrodes shows further enhancement of H2 throughput, leaving a niche for the prototype to scale‐up H2 production. Abstract : The electrochemical reforming of ethanol (produced from biomass or wastes) via an alkaline electrolyte with suspended gold nanoparticles, harnessing solar power is investigated as a simple, portable, economic, green, alternative energy, and rapid technique for the generation of clean H2 fuel.